Corporate social responsibility at the margins: Firms' responses to marginal inclusion on the Vault Law 100 ranking - Jung, Wooseok; Sharkey, Amanda; Tan, David (Strategic Management Journal, 2024)
Abstract Research Summary Gaining categorical status via a ranking places firms in a new comparison group and makes their behaviors more visible, potentially exposing them to greater scrutiny. How do marginally included firms respond? In this article, we propose that firms will take action in the area of CSR in order to secure their standing, deflect potential criticism, and reduce the anxiety that arises, paradoxically, from being included in a ranking. Using a regression discontinuity design involving law firms’ pro bono policies, we find support for our arguments. Consistent with the mechanism of status anxiety, the effects of marginal inclusion are amplified for firms with greater rank volatility. However, we find no difference in pro bono hours. We discuss implications for theories involving status, CSR, and decoupling. Managerial Summary Today, firms are evaluated by rankings and ratings more frequently than ever. This continuous external surveillance heightens organizational anxieties, especially among firms that are marginally included. This study explores the strategic responses of such firms, proposing that they enhance their corporate social responsibility (CSR) efforts in order to secure their standing, conform with expectations, and preemptively counter criticism. Analyzing pro bono policies of the largest U.S. law firms, the results support this idea and suggest that the tendency is particularly salient when firms' rank positions have fluctuated significantly. The findings offer insights into how rankings affect firms' CSR strategies and their efforts to balance status and performance.